Navigating the Challenges of Commodity Traps and Platform Economies: An Assessment in the Context of the Northern Black Forest Region and Future Directions - Bernhard Koelmel; Leon Fischer; Emilia Juraschek; Levi Peuker; Noah Stemmler; Anton Vielsack; Rebecca Bulander; Henning Hinderer; Katharina Kilian-Yasin; Tanja Brugger; Ansgar Kühn; Tanja Brysch (Commodities)
The transition to battery electric vehicles (BEVs) poses significant challenges for automotive suppliers, particularly in the Northern Black Forest Region, Germany’s largest industrial area. This study examines the risk of falling into the commodity trap and the impact of platform economics on these suppliers. A VUCA (volatility, uncertainty, complexity, ambiguity) analysis is used to assess the consequences of the open platform approach promoted by the Mobility in Harmony (MIH) Consortium. The methodology is based on a comprehensive literature review on commodity traps and platform economies, as well as an analysis of the MIH Consortium’s strategies for standardizing BEV components. The results show that while the MIH Consortium’s modularization and standardization efforts can reduce costs and facilitate mass production, they also intensify competition and limit differentiation, threatening the profit margins of smaller suppliers. The study highlights the importance of strategic positioning and innovation to counter these risks. It concludes with recommendations on how automotive suppliers can adapt to the evolving environment and be agile in responding to new technological standards and market dynamics.